Terrorism on Asean’s economic growth, does it matter? - Mertha Pessela; Erika Haryulistiani Saksono (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study provides the impact of terrorism, investment, and government expenditure on economic growth in four ASEAN countries (Indonesia, Philippines, Thailand, and Myanmar). The fix effect model indicates that terrorism and investment have a negative and significant effect on economic growth, while government expenditure has a significant positive impact.